Anopheles mosquitoes in Mondulkiri forest, Cambodia: abundance, distribution, seasonal patterns and Plasmodium prevalence - Sebastien Boyer; Bros Doeurk; Antsa Rakotonirina; Sophy Chy; Chantrea Vong; Eakpor Piv; Baura Tat; Malen Ea; Chansophea Chhin; Sreyvouch Phen; Nimol Kloeung; Sopheakvatey Ke; et al. (Malaria Journal)
Abstract Background Mosquitoes are important drivers of infectious diseases transmission, with Anopheles mosquitoes being responsible of malaria transmission. In Cambodia, where malaria is prevalent in forested regions, understanding the ecology of these vectors is crucial. This study aimed to investigate the abundance, distribution, seasonal patterns, biting behaviour of Anopheles mosquitoes, and prevalence of Plasmodium, in Mondulkiri province, Northeastern Cambodia. Methods Conducted in 9 sites, seven in forested and two in neighbouring villages, over one year, the collection of Anopheles mosquitoes was made hourly for a 72-h period every month, using a human-baited double net trap. Each mosquito was collected using a mouth-aspirator and identified morphologically, and screened for the presence of Plasmodium. Results Primary vectors, including Anopheles baimaii, Anopheles dirus, Anopheles maculatus, and Anopheles minimus, constituted 11.1% of all female mosquitoes, while 12 secondary vector species represented 29.4% of the overall collection. Anopheles species were more prevalent during the late rainy season (August to November), with year-round activity observed. Primary vectors were predominantly found in forest sites, while other vector species were found in both village and forest environments. Notably, primary vectors exhibited a preference for nocturnal biting, yet a significant proportion (19.2%) displayed daytime activity, highlighting a potential risk of daytime malaria transmission. Among 5,056 Anopheles specimens tested, only 36 Plasmodium spp.-infected samples were detected, mainly in forest sites (94%), and in specimens collected at night. This study provides essential insights into the ecology of Anopheles in Mondulkiri Forest. Conclusions The identification of primary and secondary vectors, their seasonal dynamics, and biting behaviour contribute to enhances our understanding of malaria transmission risks in these areas, guiding future strategies toward effective and context-specific control measures, while stressing the need for individual protection during daytime.